Antibacterial activity and mechanism of 460–470 nm light-emitting diodes against pathogenic bacteria and spoilage bacteria at different temperatures. (May 2021) - Hyun, Jeong-Eun; Moon, Sung-Kwon; Lee, Sun-Young
Abstract: This study was conducted to understand the antibacterial mechanisms of 460–470 nm light-emitting diode illumination (460/470 LED-illum) on Escherichia coli O157:H7, Pseudomonas fluorescens, and Listeria monocytogenes at 4 and 25 °C at a total dose of 287 J/cm 2 460/470 LED-illum significantly reduced levels of E. coli O157:H7, P. fluorescens, and L. monocytogenes in phosphate-buffered saline by 5.41, 1.57, and 5.81 log10  CFU/mL at 4 °C, respectively. Higher levels of intracellular ROS and lipid peroxidation were observed in E. coli O157:H7 and L. monocytogenes than P. fluorescens following 460/470 LED-illum. In addition, membrane depolarization and damage of E. coli O157:H7, P. fluorescens, and L. monocytogenes treated with 460/470 LED-illum were induced by oxidative stress. Furthermore, a DNA integrity assay clearly showed that 460/470 LED-illum caused the damage of cellular constituents, such as DNA. This result was consistent with the decrease in the microbial populations by LED treatment. Our findings suggest that the cell membrane is a major target of intracellular ROS during 460/470 LED-illum and causes damage to the membrane and cellular DNA. These results could provide the fundamental information about the potential technology to control pathogenic bacteria using LED with blue wavelengths. Highlights: LED could inhibit the growth of E. coli O157:H7, P. fluorescens, L. monocytogenes. Bacterial growth inhibition by LED was more effective at 4 °C than at 25 °C. LED induces intracellular ROS and adversely affects lipids in cell membrane. Higher levels of ROS lead to more depolarization and damage of cell membrane. LED cause damage of intracellular constituents such as DNA.